2018
DOI: 10.1149/08513.1013ecst
|View full text |Cite
|
Sign up to set email alerts
|

Neutron Radiographic Investigations on the Effect of Hydrophobicity Gradients within MPL and MEA on Liquid Water Distribution and Transport in PEMFCs

Abstract: In-Plane neutron radiography imaging technique was performed to investigate the effect of hydrophobicity gradients within catalyst layers (CLs) and cathode microporous layer (MPL) on water dynamics of polymer electrolyte membrane fuel cell (PEMFC) during operation. Effect of varying operating conditions (current density and relative humidity) of the inlet gases on the water content of the cells were evaluated. Hydrophobization of catalyst layers improved the membrane humidification, especially at more dry cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
(23 reference statements)
2
7
0
Order By: Relevance
“…Lee et al 18 observed the water transport with X-ray radiography and found that MPL improves the performance and reliability of the fuel cell and prevents the flooding. Mohseninia et al 19 studied the effect of MPL on water transport with neutron radiography and further proved that the MPL could cause water back diffusion from the cathode to the anode side. Similar conclusion was also drawn by Kim et al 20 that MPL can decrease the mass transport resistance and maintain a high water-content in the membrane even in low anode humidification condition by back diffusion.…”
mentioning
confidence: 99%
“…Lee et al 18 observed the water transport with X-ray radiography and found that MPL improves the performance and reliability of the fuel cell and prevents the flooding. Mohseninia et al 19 studied the effect of MPL on water transport with neutron radiography and further proved that the MPL could cause water back diffusion from the cathode to the anode side. Similar conclusion was also drawn by Kim et al 20 that MPL can decrease the mass transport resistance and maintain a high water-content in the membrane even in low anode humidification condition by back diffusion.…”
mentioning
confidence: 99%
“…In addition to the hydrophobic MPL acting as a barrier against the transfer of water to the cathode side, one can also hypothesize that under the channels the reaction rates are higher and cathode catalyst layer is at a higher temperature than anode CL; therefore, phase‐change‐induced flow shifts the water peak towards the anode. This result is also compatible with our previous neutron radiographic studies on the behavior of water dynamics of cells with hydrophobic MEA and MPL components where the hydrophobized MPL on cathode side decreased the transfer of water to the cathode channels, and subsequently has imposed the water to the opposite side .…”
Section: Resultsmentioning
confidence: 99%
“…SEM images of the home-made perforated MPLs and the commercial 29 BC (MPL and substrate side) are depicted in Figures 3 and 4, respectively. A more detailed description of the fabrication processes of the reference CL and MPL was presented in previous articles [21,47,48]. The components of the cells containing the perforated layers are listed in Table 2.…”
Section: Materials Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutron imaging has been used as a state‐of‐the‐art technique for visualizing liquid water in operating PEMFCs with a high special resolution . Several groups have successfully employed neutron tomography to advance the understanding of the relationship between liquid water behavior and the complex structural heterogeneity of porous media …”
Section: Components Of the Cellmentioning
confidence: 99%